Exploring Robert Frost’s ‘The Road Not Taken’ Using New Criticism - Febriyantasari, Devinda Aralia; Yulistiyanti, Yulistiyanti (Universitas Negeri Makassar, 2024)
Abstract. The Road Not Taken by Robert Frost is one of a famous and widely studied poem which contains several ambiguous elements that led to multiple interpretations of the poem. This study attempts to find out the theme, figurative languages, ambiguity and symbolism in The Road Not Taken by Robert Frost and its contribution to the exploration of themes. This study used text-oriented approach with qualitative data analysis techniques to delve into the textual content. In addition, this study examines Robert Frost The Road Not Taken using New Criticism theory by John Crowe Ransom and adopts a close reading methodology. The theme of the poem is choices in life specifically in making decision. Robert Frost uses symbolisms, ambiguities, and figurative languages to portray indecision, confusion, impact, and consideration in building the theme choices in life to make the best decision possible. Through a New Criticism analysis, this study aims to provide a fresh perspective and offer a more nuanced understanding of the poem’s meaning. This study aims to engage scholars, researchers, and students in the analysis and interpretation of poem, leading to new insight, theories, and discussions within the field of literary studies. The global implications of this study include a better knowledge of literary analysis methodologies as well as insights into how great poems continue to affect modern conversations about life choices and decision-making. Keywords: New Criticism, Ambiguity, Symbolism, Figurative Language, Theme